Investigating the presence of equine piroplasmosis in Ireland. (4th September 2020) - Coultous, Robert M; Leadon, Desmond P; Shiels, Brian R; Sutton, David; Weir, William
Abstract : Background: Equine piroplasmosis (EP) is a notifiable disease in Ireland and a significant concern to domestic and international equine industries. Information regarding EP presence in Ireland is currently limited. This retrospective surveillance study describes a serological and molecular analysis of blood samples submitted to the Irish Equine Centre for EP testing between January 2013 and April 2016. Methods: Following serological testing, seropositive samples were screened using a PCR targeting the 18S ribosomal RNA gene. Amplicon sequences were bioinformatically analysed to identify the parasite species and to assess genetic diversity. Results: From 2099 screened equine blood samples, 2.5 per cent and 1 per cent were seropositive for Theileria equi and Babesia caballi, respectively. T equi DNA was detected in 9 per cent of the seropositive samples while B caballi DNA was not detected in any sample. The T equi DNA sequences displayed no genetic diversity at this locus, in contrast to samples from the UK and from endemic areas. Conclusion: Detection of EP‐seropositive and parasitaemic horses in Ireland indicates a clear and present health risk to the equine population. It is recommended that owners adopt appropriate biosecurity measures and that clinicians are mindful of this disease as a differential diagnosis.